2019
DOI: 10.1111/1759-7714.13240
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and treatment of immune checkpoint inhibitor‐associated pneumonitis

Abstract: The increasing use of immune checkpoint inhibitors in tumors has brought new hope of survival to patients with advanced tumors. However, the immune system activated by immune checkpoint inhibitors, mainly activated T‐cells, can attack normal tissues and organs in the body and lead to a variety of adverse effects. In the lung, these attacks can induce checkpoint inhibitor pneumonitis (CIP). CIP is different from known pulmonary interstitial pneumonitis, and has the potential to be fatal if not treated correctly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 19 publications
0
66
1
Order By: Relevance
“…Although smoking history was not identified as a risk factor of ICI-ILD in this study, unlike drug-induced ILD 13 , ≥ 50 pack-year was associated with the development of ICI-ILD of all grades. This result suggested that when treating lung cancer with ICI, the presence or absence of smoking history and quantitative assessments of smoking should be considered.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Although smoking history was not identified as a risk factor of ICI-ILD in this study, unlike drug-induced ILD 13 , ≥ 50 pack-year was associated with the development of ICI-ILD of all grades. This result suggested that when treating lung cancer with ICI, the presence or absence of smoking history and quantitative assessments of smoking should be considered.…”
Section: Discussioncontrasting
confidence: 65%
“…not continue ICI treatment and to achieve treatment benefits in patients with lung cancer. However, only a few studies have reported that the development of ICI-ILD was prevented 13 .…”
mentioning
confidence: 99%
“…However, a specific pattern cannot be defined in some cases [60]. In fact, given the variability of the radiographic features, the possibility of ICI-related pneumonitis should be assessed whenever new non-massive imaging changes are found on chest CT of patients treated with ICI [80]. Special attention should be raised upon the radiologic features that may appear in patients with preexisting lung fibrosis (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…Combination therapy of PD‐1/PD‐L1 and CTLA‐4 inhibitors carries a higher risk of pulmonary toxicity, with an incidence of 6.88% for all grade pneumonitis and 1.88% incidence for grade 3–4 58 . While validated risk factors for pulmonary are currently unknown, there is thought that characteristics such as sex, age, smoking history and baseline lung disease may predispose patients 59 . Studies have observed that patients with baseline interstitial lung disease have increased risk, as well as tumour type, such as lung and renal cell carcinoma, may lead to an increased incidence of pulmonary toxicity 60,61 .…”
Section: Introductionmentioning
confidence: 99%